An review of research on liquid hydrogen leakage: regarding China’s hydrogen refueling stations - Rong, Yangyiming; Yuan, Wenhao; Peng, Jianbin; Hou, Jiaxin; Gao, Jun; Zhang, Xiang; Chen, Jianye; Chen, Shunyi (Frontiers in Energy Research, 2024)
Hydrogen is regarded as the premier energy source for future sustainability and renewability. However, its distinct physicochemical properties render it prone to explosions in the event of a leak. Therefore, there is a need for more comprehensive research dealing with hydrogen leakage, explosion scenarios, and risk assessment. This paper provides an overview of the current hydrogen policies adopted in China. It reviews the processes of hydrogen refueling station construction and the thermophysical mechanisms of liquid hydrogen leakage. In this regard, the effects of various factors, including leakage rate, leakage time, leakage hole size, wind direction and speed, and building location, on the hydrogen leakage rate are analyzed and evaluated. Additionally, the impacts of different factors on hydrogen explosion overpressure are reported, including hydrogen concentration, wind speed, obstacles, and ignition position, in addition to the current applications of quantitative risk assessment methods in hydrogen refueling stations. Finally, the limitations of current research on liquid hydrogen leakage and explosion accidents are highlighted, along with the shortcomings of current risk assessment methods for liquid hydrogen refueling stations.